Experimental Evolution and Hybridization Enhance the Fermentative Capacity of Wild Saccharomyces Eubayanus Strains - Cubillos-Riffo, F; Vega-Macaya, F; Oporto-Donoso, C; Villarreal-Diaz, P; Pena-Echeverria, T (Oxford University Press, 2025)
Lager beer is traditionally fermented using Saccharomyces pastorianus. However, the limited availability of lager yeast strains restricts the potential range of beer profiles. Recently, Saccharomyces eubayanus strains showed the potential to impart novel aromas to beer, with slower fermentation rates than commercial strains. Here, we applied experimental evolution to nine S. eubayanus strains using three different selective conditions to generate improved strains to fermentative environments. We observed environment-dependent fitness changes across strains, with ethanol-enriched media resulting in the greatest fitness improvement. We identified subtelomeric genomic changes in a deficient fermentative strain underlying the greatest fitness improvement. Gene expression analysis and genome sequencing identified genes associated with oxidative stress, amino acid metabolism, sterol biosynthesis, and vacuole morphology underlying differences between evolved and the ancestral strain, revealing the cellular processes underlying fermentation improvement. A hybridization strategy between two evolved strains allowed us to expand the phenotypic space of the F2 segregants, obtaining strains with a 13.7% greater fermentative capacity relative to the best evolved parental strains. Our study highlights the potential of integrating experimental evolution and hybridization to enhance the fermentation capacity of wild yeast strains, offering strengthened solutions for industrial applications and highlighting the potential of Patagonian S. eubayanus in brewing. © 2025 The Author(s).